Shear bond strength of ceramic and metal brackets bonded to enamel using color-change adhesive - Mohadeseh Delavarian; Farshad Rahimi; Ramin Mohammadi; Mohammad Moslem Imani (Wolters Kluwer Medknow Publications, 2019)
Background: This study aimed to compare the shear bond strength (SBS) of ceramic and metal brackets bonded to the enamel using Grengloo color-change adhesive and Transbond XT conventional composite. Materials and Methods: In this in vitro, experimental study, 120 extracted human premolars were divided into four groups: (1) Grengloo with metal brackets, (2) Grengloo with ceramic brackets, (3) Transbond XT with metal brackets, and (4) Transbond XT with ceramic brackets. After bracket bonding, the teeth were subjected to 500 thermal cycles and incubated at 37°C for 24 h. The SBS was measured and the data were analyzed using two-way ANOVA. Mann-Whitney U test was used to compare the Adhesive Remnant Index (ARI) scores. was statistically significant (P < 0.001) Results: The effect of type of bracket (metal/ceramic) on SBS was not statistically significant (P = 0.368). However, the effect of type of composite on SBS was statistically significant (P < 0.001) and the SBS of Grengloo was higher than that of Transbond XT. No significant difference was found in ARI scores among the groups. Conclusion: Regarding the high SBS and the safe region of bond failure in Grengloo composite, this color-change adhesive can be a suitable alternative in cases that require high bond strength. Furthermore, the color contrast of Grengloo can make composite removal easier than Transbond XT with color match of composite and teeth.